Thermo‐ and pH‐sensitive triblock copolymers with tunable hydrophilic/hydrophobic properties. Issue 22 (25th June 2015) - Pottier, Christophe; Morandi, Gaëlle; Dulong, Virginie; Souguir, Zied; Picton, Luc; Le Cerf, Didier
ABSTRACT Polymers consisting of poly(acrylic acid) (PAA) and statistical poly[(acrylic acid)‐co‐(tert‐butylacrylate)] (P(AA‐co‐tBA)), attached to both extremities of Jeffamine® (D series based on a poly(propylene oxide) (PPO) with one amine function at each end) using atom transfer radical polymerization (ATRP) are presented in this article. An original bifunctional amide‐based macroinitiator was first elaborated from Jeffamine®. tBA polymerization was subsequently initiated from this macroinitiator. This polymerization occurs in a well‐controlled manner leading to narrow molecular weights distribution. Amphiphilic copolymers were finally obtained after complete or partial hydrolysis of the PtBA blocks into PAA. The control of the partial hydrolysis of tBA units, conducted in a concentrated HCl/tetrahydrofuran mixture, is demonstrated. The properties of the triblock copolymers were preliminary investigated in aqueous solution by absorbance, DLS measurements and SEC/MALS/DV/DRI analysis as a function of temperature and pH modifications, providing evidences of thermo‐ and pH‐sensitive self‐assembly of the copolymers. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 2606–2616